2007
DOI: 10.1088/0953-4075/40/13/004
|View full text |Cite
|
Sign up to set email alerts
|

Post-collisional effects on single ionization in 75 keV p + He collisions

Abstract: We report fully differential cross-section calculations using distorted wave theories for helium single ionization by 75 keV p impact. Comparisons are made with absolute experimental data and we find that good results are obtained in the magnitude without the need for normalization factors. However, discrepancies are quite apparent in the position and shape of the peak structures in the fully differential angular distribution of the ejected electrons. We assess the influence of the internuclear interaction on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 38 publications
2
43
0
Order By: Relevance
“…3 show CDW-EIS calculations, which account for the PT interaction semiclassically in terms of the eikonal approximation assuming a classical straight-line trajectory of the projectile [42]. Higher-order contributions from the projectile-electron interaction are treated in terms of a distortion of the ejected electron wave by the projectile in the final state and in terms of an eikonal phase factor in the initial state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 show CDW-EIS calculations, which account for the PT interaction semiclassically in terms of the eikonal approximation assuming a classical straight-line trajectory of the projectile [42]. Higher-order contributions from the projectile-electron interaction are treated in terms of a distortion of the ejected electron wave by the projectile in the final state and in terms of an eikonal phase factor in the initial state.…”
Section: Resultsmentioning
confidence: 99%
“…Here too, non-negligible discrepancies to experimental data remain. Otherwise, although promising nonperturbative models without the PT interaction were developed recently [39,40], at present only perturbative approaches accounting for the PT interaction in the final-state wave function can be compared to experiment (e.g., [5,17,[41][42][43][44][45]). However, it was pointed out that the PT interaction, which is contained in the final-state wave function in these models, is only described accurately if at least one collision fragment is far from the other two fragments [46,47], which is not a likely constellation for electron ejection into the perpendicular plane [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Schultz et al [12] measured the FDCS for single ionization of Helium by 75-keV proton impact. Their experimental results were compared to data of various distorted wave calculations, including the continuum-distorted wave with eikonal initial state (CDW-EIS) approximation [13][14][15][16]. The important role of interaction between the nuclei has been observed, and reasonably accounts of the measured FDCS were reported mostly in the collisions plane.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, within the CDW-EIS scheme, it is possible to incorporate the interaction between the heavy nuclei, also known as N-N interaction, in a semiclassical way [26]. It has been shown that this approach is able to reproduce with reasonable agreement fully differential cross sections (FDCS) for single ionization of helium by heavy ions in a broad range of projectile velocities (see, e.g., [27][28][29][30]). …”
Section: Introductionmentioning
confidence: 99%